The Eclipse of Morality: A Riposte to Lane, Wildman, & Shults’ “Paying the Piper” Commentary - Ambasciano, Leonardo (Method & theory in the study of religion, 2023)
The present contribution is a riposte to Lane, Wildman, and Shults’ commentary on my MTSR article “He Who Pays the Piper Calls the Tune” (Ambasciano 2022). I offer an epistemological and historical criticism of some of their most relevant claims, along with the identification and deconstruction of some of the biases and fallacies behind their commentary. I also highlight – once again – the historiographical neglect and some of the most questionable approaches and unresolved issues in the current CSR 2.0 modus operandi. Along with the ethical and financial impact of private donors with political and religious agendas in the field, such controversial topics call for immediate action from peers and associations to avoid the further drain of money, resources, and personnel in a time of increasing financial austerity. A computational science incapable of confronting and resolving such basic issues is not a computational science at all – it’s mere tech-evangelism.